Психологический способ коррекции страха и тревоги перед стоматологическими вмешательствами (Эндодонтия Today, 2020)
According to research data a considerable part of the adult population is afraid of dental procedures, visiting the dentist for them is a psychological and emotional stress. During treatment these patients can manifest changes in hemodynamic, respiratory, blood sugar, increased sweating and other autonomic responses, exacerbate the already existing somatic pathologies that affect the performance of dentists procedures and reduce the quality of his or her medical services. Provision of psychological comfort for the patient is an important component of safety of dental treatment. The authors have developed the principles and algorithms of the distress correction, including a system of verbal instructions and commands, during dental treatment.